Powerful guiding coalitions : how to build and sustain the leadership team in your PLC at work - Hall, Bill (Educator) (Solution Tree Press, 2022)
"Leading a school is a tall order, and leading a school transitioning into a professional learning community is a journey not taken alone. Bill Hall's Powerful Guiding Coalitions: How to Build and Sustain the Leadership Team in Your PLC examines what it means to be a powerful guiding coalition, and how to create such a team, develop it, and sustain it. This book serves as a resource for schools beginning their journey to becoming a PLC, schools already on the path, and schools looking to get back on track. It is a guide for principals and other school leaders, as well as a resource for members of a guiding coalition"--